Navigating the new globalization proceedings of the Fifth Annual Public Policy Conference 2019. (Philippine Institute for Development Studies, 2020)
The New Globalization has reached the Philippine shores. To assist the country in crafting relevant policies on this phenomenon, the fifth Annual Public Policy Conference (APPC) became the stage for a critical analysis of the issues surrounding this new phase of growth. Among others, it emphasized globalization's impact on Philippine trade, environment, public health, equity, social cohesion, and information sharing.